Population size may shape the accumulation of functional mutations following domestication - Jianhai Chen; Pan Ni; Xinyun Li; Han Jianlin; Jakovlić, Ivan; Chengjun Zhang; Shuhong Zhao (Springer, 2018)
Background Population genetics theory predicts an important role of differences in the effective population size (N e ) among species on shaping the accumulation of functional mutations by regulating the selection efficiency. However, this correlation has never been tested in domesticated animals. Results Here, we synthesized 62 whole genome data in eight domesticated species (cat, dog, pig, goat, sheep, chicken, cattle and horse) and compared domesticates with their wild (or ancient) relatives. Genes with significantly different selection pressures (revealed by nonsynonymous/synonymous substitution rate ratios, Ka/Ks or ω) between domesticated (Dω) and wild animals (Wω) were determined by likelihood-ratio tests. Species-level effective population sizes (N e ) were evaluated by the pairwise sequentially Markovian coalescent (PSMC) model, and Dω/Wω were calculated for each species to evaluate the changes in accumulation of functional mutations after domestication relative to pre-domestication period. Correlation analysis revealed that the most recent (~ 10.000 years ago) N e (s) are positively correlated with Dω/Wω. This result is consistent with the corollary of the nearly neutral theory, that higher N e could boost the efficiency of positive selection, which might facilitate the overall accumulation of functional mutations. In addition, we also evaluated the accumulation of radical and conservative mutations during the domestication transition as: Dradical/Wradical and Dconservative/Wconservative, respectively. Surprisingly, only Dradical/Wradical ratio exhibited a positive correlation with N e (p < 0.05), suggesting that domestication process might magnify the accumulation of radical mutations in species with larger N e .